EXAMINING PERSONNEL’S UNDERSTANDING OF HANDLING UNUSED AND EXPIRED MEDICATION - Siti Nur Fathini Muhsain; Siti Nur Fadzilah Muhsain; Fatin Nursyahira Fadillah; Sumayyah Mohamad Nordin; Siti Nor Syuhaidah Basri; Ahmad Akhtar Ihsan A’ahmad Jamili, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
In recent times, there has been a notable increase in medication wastage, encompassing medications that expire or remain unused across the entire supply chain. This waste also includes instances of unnecessary or inappropriate medication consumption by patients, as well as non-adherence to treatment guidelines by healthcare professionals. Such wastage imposes financial burdens on both patients and the economy, necessitating comprehensive education efforts across all involved parties. The objective of this research is to examine the knowledge of handling unused and expired medication among the staff at UiTM Cawangan Pulau Pinang (UiTMCPP). An online questionnaire survey was conducted among the staff. The primary reason cited by respondents for keeping medications at home was for future use and the sense of security in having a stock of medication at home. The common action taken with expired medication was disposal in household garbage, with only 27 respondents indicating a preference for returning expired drugs to pharmacies. The most preferred sources of information regarding the proper handling of expired and unused medication were the Ministry of Health and pharmacists. In conclusion, this study emphasizes the importance of addressing the perceived awareness of medication handling among staff at UiTM Bertam. The university administration must take proactive measures to enhance awareness among its staff members.